Pengaruh Kompetensi Guru Shadow Terhadap Indikator Penilaian Pada Sekolah Inklusi MI Terpadu Ar-Roihan - Melisa Wahyu Fandyan Sari; Tities Hijratur Rahmah (Proceedings of The ICECRS, 2018)
This study aims to "know the effect of teacher shadow competence on indicator value ", formulation of the problem "how the effect of teacher shadow competence on indicator value ". Inclusion schools are public schools that combine regular students with ABK students. In general, teacher competence is divided into four, namely competence: 1) pedagogy, personality, social and professional. But for shadow teachers there are additional competencies that should be mastered that is performative competence. Requirements for teachers to master performative competence are to understand and understand the circumstances surrounding the environment, plan goals and strategies, transmit positive values to the environment, create message intelligence. The assessment of shadow teachers at MIT Ar-Roihan has the name of the indicator value, consisting of eight aspects of the assessment, namely: 1) making learning tools, 2) learning implementation, 3) learning evaluation, 4) reporting learning outcomes, 5) attitudes, 6) making media, 7) additional tasks, and 8) special achievements. This research is a correlational quantitative research, location at MIT Ar-Roihan Lawang, Malang Regency. The sample of the research used total sampling technique with 37 teachers. Data analysis using linear regression technique. From the results, obtained correlation coefficient value R = 0,596 and included medium category. From the table "ANOVA", obtained Regression value is 0.000 and <0,05 then concluded "There is a significant influence between teacher shadow competence (X) on indicator value (Y)".